The capitalist commodification of animals - Clark, Brett; Wilson, Tamar Diana (Research in political economy ;, 2020)
While animal suffering and abuse have taken place throughout history, the alienation of humanity from nature caused by the development of capitalism - by the logic of capital and its system of generalized commodity production - accelerated and increased the depredations in scope and scale. The capitalist commodification of animals is extensive. It includes, but is not limited to: livestock production in concentrated animal feeding operations leather and fur production the ivory trade in which tusks are used for 'traditional medicines; or carved into decorative objects entertainment such as in zoos, marine parks, and circuses laboratory experimentation to test medicines, beauty products, pesticides, and other chemicals the pursuit of trophy hunting, sometimes on canned farms and sometimes in the wild bioengineering of livestock and of animals used in laboratories The contributors to this special issue of Research in Political Economy provide insightful analyses that address the historical transformations in the material conditions and ideological conceptions of nonhuman animals, alienated speciesism, the larger ecological crisis that is undermining the conditions of life for all species, and the capitalist commodification of animals that results in widespread suffering, death, and profits. This book is a must-read not only for political economists, but also for researchers interested in animal studies, environmentalism, and sustainability.